2015
DOI: 10.3109/15376516.2015.1045661
|View full text |Cite
|
Sign up to set email alerts
|

Unusually high levels of bisphenol A (BPA) in thermal paper cash register receipts (CRs): development and application of a robust LC-UV method to quantify BPA in CRs

Abstract: We have developed a simple, reversed-phase high-performance liquid chromatography (RP-HPLC) method for the determination of bisphenol A (BPA) in thermal paper cash register receipts (CRs). The method is suitable for analysis of other types of bisphenols and it involves an overnight extraction of CRs with acetonitrile (AN) at 50 °C followed by the HPLC analysis on a Supelcosil LC18 column (150 × 4.6 mm, particle size: 5 μ) using 50% AN in water as the mobile phase (5 min, isocratic). The composition of AN in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…BPA is a component of polycarbonate plastics used in food and beverage containers and epoxy resins used to line food cans and for dental materials. High levels of BPA are also found in carbonless paper [7], and BPA has been measured in ground water, soil, dust and air (reviewed in Ref. [8]).…”
Section: Introductionmentioning
confidence: 99%
“…BPA is a component of polycarbonate plastics used in food and beverage containers and epoxy resins used to line food cans and for dental materials. High levels of BPA are also found in carbonless paper [7], and BPA has been measured in ground water, soil, dust and air (reviewed in Ref. [8]).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding sources of BPA exposure is instrumental for identifying populations at greatest risk and for devising strategies for reducing exposure. Studies measuring BPA in food and paper products have found levels as high as 730 ng/g in food (e.g., canned green beans) [ 26 ], 26.6 ug/g in food-contact paper [ 10 ] and 42.6 mg/g in thermal receipt paper [ 6 ]. Higher urinary concentrations of Total BPA have been associated with cashier-related occupations in pregnant women [ 27 ] and the general population [ 28 , 29 ], with consumption of canned vegetables, hamburgers and soda in pregnant women [ 25 ], and with consumption of soda and meals prepared outside the home in the general U.S. population [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…BPA in thermal papers are loosely bounded in monomeric forms that can be readily transferred to any surface that comes in contact even by touching them with our hands. In addition, BPA in thermal papers does not require any harsh acidic or heat conditions to facilitate migration from the source (Babu et al 2015). Even though nobody usually soaks thermal papers in water, but due to improper recycling process or bad disposal practices, thermal papers end up in land ll sites and also enter in water bodies.…”
Section: Resultsmentioning
confidence: 99%